A Educação Física como Ferramenta para o Desenvolvimento Pessoal - Pedro Xavier Carvalho (2024)
The aim of this study is to present the entire process that took place over the course of a school year as part of the School Placement course, which is part of the master's program for Teaching Physical Education in Primary and Secondary Schools. Internships have an important value because they serve as a conclusion to a journey carried out throughout university education and which aims to train teachers in teaching and at the same time create an impact on what the future reality of a Physical Education teacher will be like. All the knowledge acquired over three years of undergraduate study and a master's degree is put to the test over the course of a school year, in which we are asked to teach two primary or secondary school classes. This internship took place at the António Nobre Secondary School in the district of Porto, where I was assigned two secondary school classes. A 10th year professional education class and a 12th year regular education class. I'm going to look at the main differences between these two types of education and try to understand the main motivations that lead students to take Physical Education classes. This study is divided into five parts, starting with the Personal Framework, the Framework for Practice, the Realization of Professional Practice, which will provide a framework for the school year that has passed and all the resources that have been provided for me to teach, followed by a research study on the Impact of Physical Education on Students' Academic and Personal Lives, with the aim of analyzing the students' opinions in relation to Physical Education classes and the main reasons for their participation and dedication to Physical Education, and culminating with a brief Conclusion and Future Prospects. The main aim of this document is to transmit all the achievements and difficulties that have emerged over the course of this year and to demonstrate the passion I feel for teaching. It also demonstrates the importance of Physical Education in students' daily lives and why we should continue to fight for equality with other curricular subjects. I hope this document is as easy to understand and conclusive as possible and that it shows that my journey as a teacher has just begun and that it will always be a process of constant learning and development, both professionally and personally.